1972
DOI: 10.1136/pgmj.48.559.295
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of renal tubular defects in old age

Abstract: SummaryThe mechanisms of renal tubular dysfunction in old age have been examined in twenty-eight clinically healthy elderly subjects without infection, and in fourteen subjects of similar age with laboratory evidence of intrarenal infection. The data were compared with those from thirteen clinically healthy young subjects. Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…It has been demonstrated that both age and vascular disease correlate independently with the percentage of hyalinized glomeruli in the aged [13]. Indeed, in some studies the renal blood flow declined progressively at a rate of approximately 10% per decade, starting after the 4th decade [5,20].…”
Section: Anatomy and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that both age and vascular disease correlate independently with the percentage of hyalinized glomeruli in the aged [13]. Indeed, in some studies the renal blood flow declined progressively at a rate of approximately 10% per decade, starting after the 4th decade [5,20].…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…The proximal tubular volume of individual nephrons tends to decrease from a mean of 0.076 mm 3 at 20-39 years to a mean of 0.059 mm 3 at 80-101 years [12]. Since the loss of the glomerular mass is proportional to the loss of the tubular mass, the glomerulotubular balance is, in general, well preserved [5,13].…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…Loss of nephrons in the aging kidney that result in an obligatory solute diuresis and an intrinsic defect in solute transport in the diluting segment of the nephron impose inherent restrictions on the minimal osmolality that the renal tubule can establish. 38 Although the ability to excrete an acute salt and water load is dependent on factors intrinsic to the kidney, overwhelmingly so is the ability to suppress antidiuretic hormone release and maintain a waterimpermeable segment in the terminal nephron. Thus, an inappropriate, nonosmotic release of antidiuretic hormone that is common to sick elderly patients, coupled with an intrinsic defect in urinary dilution and a decline in glomerular filtration, will also potentiate excessive water retention and predispose to the prolonged overexpansion of extracellular water seen in elderly, critically ill patients.…”
Section: Commentmentioning
confidence: 99%
“…A potent COX-1 and COX-2 inhibitor as indomethacin was markedly decreased in the synthesis of vasodilatory PG in a renal ablation model than a selective COX-2 inhibitor (7). In elderly patients, renal blood flow (24,25) and urinary PGI 2 excretion (26) were decreased. Taken together with these findings, short-term administration of DF, but not LP induced renal ischemia, as a result, the renal function was impaired in elderly patients after LRN.…”
mentioning
confidence: 99%